Foreign aid projects and trust in political institutions. Issue 3 (21st July 2021) - Watkins, Mitchell
Abstract: Do foreign aid projects undermine citizens' trust in local and national political institutions? Drawing on institutional theories of political trust, I hypothesize that foreign aid projects reduce trust in political institutions by lowering citizens' perceptions of government performance and raising perceptions of corruption. To analyze the impact of aid projects on trust, this article utilizes geolocated survey data on citizens' trust in political institutions from Afrobarometer Rounds 2–5 (2003–2012) and data on the location of foreign aid projects from AidData's Aid Information Management Systems datasets for Nigeria, Senegal, and Uganda. Using a spatial difference‐in‐difference strategy, the empirical results find that active aid projects are on average associated with decreased trust in the president, parliament, and local government council. An exploratory sectoral analysis suggests that the negative average treatment effect is driven by projects in the transportation, agriculture, education, and civil society sectors.